Determinants of Islamic Social Reporting in Indonesian Islamic Commercial Banks - Diah Rositasari; Dita Andraeny (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The purpose of this study is to analyze the effect of firm size, firm age, board of commissioners size, and leverage on the level of disclosure of Islamic Social Reporting (ISR) at Islamic Commercial Banks in Indonesia in the period 2018-2023. The method applied in this research is a quantitative approach with panel data regression analysis, which adopts a regression model known as the Random Effect Model (REM). Sampling through purposive sampling, with the criteria that Islamic Commercial Banks are consistently registered with the OJK from 2018-2023 and banks that provide complete annual reports during that period, and obtained the results of 10 banks with a total of 60 data observations. The data used is taken from the annual reports published on the official website of each bank for 2018-2023. The analysis shows that firm size and board of commissioners size have a positive influence on ISR disclosure. In contrast, firm age has a negative influence, while leverage does not show a significant influence on ISR. The limitations of this study are that it only focuses on several factors that influence the disclosure of Islamic Social Reporting. Future research can consider other factors to obtain comprehensive results.